2014
DOI: 10.1039/c4cc04476b
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected cluster formation upon hydroboration of a neutral diborene with 9-BBN

Abstract: The reaction of the neutral, base-stabilised diborenes 1a,b with the well-known hydroboration reagent 9-borabicyclo[3.3.1]nonane (9-BBN) is presented. This leads to the formation of a nonclassical structural motif with a B3 core concomitant with the cleavage of a B-C bond. This compound has been characterised in solution and by X-ray crystallography. According to Wade's rules these rare B3 clusters follow the arachno classification (2n + 6 electrons) and represent doubly base-stabilised B3H5 analogues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0
11

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 29 publications
0
32
0
11
Order By: Relevance
“…[101] 5.5. [103] This divergent reactivity was tentatively assigned to the lack of electronic stabilization at the trigonal 9-BBN fragment after the initial hydroboration step,prompting the formation of multicenter bonds. Hydroboration Thea ddition of E À Hb onds across unsaturated carboncarbon multiple bonds,n otable examples of which include hydroboration, hydroamination, and hydrogenation, is hugely important for the functionalization of organic molecules.…”
Section: Redox Chemistrymentioning
confidence: 99%
“…[101] 5.5. [103] This divergent reactivity was tentatively assigned to the lack of electronic stabilization at the trigonal 9-BBN fragment after the initial hydroboration step,prompting the formation of multicenter bonds. Hydroboration Thea ddition of E À Hb onds across unsaturated carboncarbon multiple bonds,n otable examples of which include hydroboration, hydroamination, and hydrogenation, is hugely important for the functionalization of organic molecules.…”
Section: Redox Chemistrymentioning
confidence: 99%
“…[13] We have thus demonstrated that Nheterocyclic carbene (NHC)-stabilized diheteroaryldiborenes undergo spontaneous syn-hydroboration with catecholborane [14] and 9-borabicyclo[3.3.1]nonane (9-BBN). [15] We have also shown that as aturated NHC-stabilized diboryne featuring aformal BBtriple bond and adiboracumulene stabilized by p-acidic cyclic (alkyl)(amino)carbene (CAAC) ligands undergo facile uncatalyzed hydrogenation to the corresponding trans-dihydrodiborenes. [16] In contrast, the direct hydrogenation of diborenes has eluded our efforts,w ith the exception of our recently reported diiododiborene, (PCy 3 ) 2 B 2 I 2 ,w hich undergoes stepwise hydrogenation, first to the rather unstable 1,2-dihydrodiborane,( Cy 3 P) 2 B 2 H 2 I 2 , and then to the (dihydro)iodoborane (Cy 3 P)BH 2 Iw ith concomitant B À Bb ond cleavage.…”
mentioning
confidence: 98%
“…Daraufhin kommt es zur Bildung eines sechsgliedri-gen Übergangzustands,w oraufhin sowohl der protische als auch der hydridische Wasserstoff in einem konzertierten Mechanismus an die ungesättigte Bindung abgegeben werden (Abbildung 1a). [13] Wirh aben dabei gezeigt, dass mit N-heterocyclischen Carbenen (NHCs) stabilisierte Diheteroaryldiborene eine spontane syn-Hydroborierung mit Catecholboran [14] und 9-Borabicyclo[3.3.1]nonan (9-BBN) [15] eingehen. Anschließend findet ein Protonentransfer zum borylierten Kohlenstoffatom statt, woraufhin das Aminoboran als Nebenprodukt freigesetzt wird (Abbildung 1b).…”
unclassified